Rituximab, cyclophosphamide, doxorubicin, vincristine and prednisolone (R‐CHOP) in the management of primary mediastinal B‐cell lymphoma: a subgroup analysis of the UK NCRI R‐CHOP 14 versus 21 trial. (1st August 2016) - Gleeson, Mary; Hawkes, Eliza A.; Cunningham, David; Chadwick, Nick; Counsell, Nicholas; Lawrie, Anthony; Jack, Andrew; Smith, Paul; Mouncey, Paul; Pocock, Christopher; Ardeshna, Kirit M.; Radford, John; et al.
Summary: We performed a subgroup analysis of the phase III UK National Cancer Research Institute R‐CHOP‐14 versus R‐CHOP‐21 (two‐ versus three‐weekly rituximab, cyclophosphamide, doxorubicin, vincristine and prednisolone) trial to evaluate the outcomes for 50 patients with World Health Organization 2008 classified primary mediastinal B‐cell lymphoma identified from the trial database. At a median follow‐up of 7·2 years the 5‐year progression‐free survival and overall survival was 79·8% and 83·8%, respectively. An exploratory analysis raised the possibility of a better outcome in those who received R‐CHOP‐14 and time intensification may still, in the rituximab era, merit testing in a randomised trial in this subgroup of patients.